We are our own sonnet / Siti Zarikh Sofiah Abu Bakar - Abu Bakar, Siti Zarikh Sofiah (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.